(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2009)
The income tax that is imposed on the salaries & wages of employees in the governmental fields &the companies of public & mixed sectors by direct deduction in a manner similar to the employees in the private sector according to the order NO.49 of 2004 issued by Coalition Provision Authority in Iraq , from the validity of Security Council resolutions NO. 1482 of 2003, &1511 of 2004. The research will discuss that the resolution of income tax deduction on the salaries &wages of employees in public sector is not suitable in timing in terms of the political, security &economic situation in Iraq and the state ability to implement lays &the patriotic sense of the tax payer, in addition to the legitimacy of the decision that was based on foreign vision & willingness, and the consequences of its implementation were not positive on the whole. The research aims to show the importance of issue of such a decision and its implementation after making Scientific, realism and deep (thorough) studies in terms of appropriate apolitical, Security and economic situations.